قياس أثر التنويع الاقتصادي على النمو الاقتصادي للفترة (1980-2021) -الجزائر كنموذج- - شرف, نصيرة (جامعة الوادي - University of Eloued, 2024)
The purpose of this research is to determine the impact of economic diversification on economic growth in Algeria in the period from 1990 to 2021, and the standard model (ARDL) was used to estimate the study model. The study concluded that there is a positive and significant impact of both industrialists in both the industrial and services sectors on economic growth in the long term. The results also showed that the agricultural sector does not affect economic growth in the long term, since its parameter is not statistically significant.
Measuring the impact of economic diversification on economic growth during (1980-2021) - Algeria as a model -
مقال
Keywords: تنويع اقتصادي ; نمو اقتصادي ; الجزائر ; نموذج ; ARDL